Parameters Associated with Significant Liver Histological Changes in Patients with Chronic Hepatitis B. (28th January 2014) - Xiao, Li; Xian, Jianchun; Li, Yang; Geng, Aiwen; Yang, Xiuzhen; Han, Libin; Xu, Hongtao
Abstract : This study aimed to evaluate factors associated with significant liver histological changes. Liver biopsies from 157 CHB patients were retrospectively analyzed. Only ALB was significantly correlated with advanced liver necroinflammatory (P = 0.001 ). Age, ALB, GLOB, AST, PLT, and PT were independent predictors of significant fibrosis (P = 0.002, P < 0.001, P = 0.001, P = 0.048, P < 0.001, and P = 0.001, resp.). AST, WBC, and HBV DNA were significantly correlated with advanced fibrosis in normal ALT patients (P < 0.001, P = 0.041, and P = 0.012, resp.) and age, ALB, GLOB, PLT, and PT in patients with abnormal ALT (P = 0.003, P < 0.001, P = 0.004, P < 0.001, and P = 0.002, resp.). Age, AST, GGT, PLT, and PT were significantly associated with advanced fibrosis in HBeAg+ patients (P = 0.01, P = 0.016, P = 0.027, P = 0.016, and P = 0.009, resp.) and ALB, GLOB, WBC, PLT, and PT in HBeAg− patients (P < 0.001, P = 0.004, P = 0.005, P < 0.001, and P = 0.035, resp.). PLT was an excellent predictor for cirrhosis (P < 0.001 and AUROC = 0.805 ). ALT was not predictive of advanced fibrosis for patients with HBeAg+ or HBeAg− (P = 0.273 and P = 0.599, resp.). PLT was an excellent predictor for cirrhosis in CHB patients. Liver histopathology can be recommended for chronic HBV carriers of older age, with normal ALT, lower PLT, and lower ALB.